Schemes of arrangement : theory, structure, and operation - Payne, Jennifer, 1970- (Cambridge : Cambridge University Press, 2021)
Schemes of arrangement are an important and flexible mechanism, which can be used to reorganise a company's capital. Schemes have undergone a renaissance over the last twenty years, particularly as a debt restructuring device in the aftermath of the 2008 financial crisis when companies and their advisors have needed to develop effective tools for dealing with financial distress. The COVID-19 pandemic has provided a further incentive for jurisdictions to ensure that they have an effective debt restructuring mechanism in place. Schemes have also become the mechanism of choice for recommended takeovers. This book performs a critical, contextual and comparative analysis of schemes and their uses, examines recent developments in this area, including the Corporate Insolvency and Governance Act 2020, and considers whether further reform is needed to ensure that schemes continue to develop as an indispensable tool for companies for the future.
The mechanics of a scheme of arrangement -- Member schemes of arrangement : takeover schemes -- Member schemes of arrangement : other examples -- Creditor schemes of arrangement : debt restructuring -- Creditor schemes of arrangement : other examples -- Cross-border issues.
Title from publisher's bibliographic system (viewed on 16 Dec 2021).
Keywords: Assignments for benefit of creditors -- Great Britain; Bankruptcy -- Great Britain; Corporate reorganizations -- Great Britain; Debtor and creditor -- Great Britain